The use of audio-visual material for accessing prior knowledge in Geography and History learning - Ramos Vallecillo, Nora; Murillo Ligorred, Víctor; Revilla Carrasco, Alfonso (Clio. History and History Teaching, 2021)
This study investigates the effectiveness of audio-visual resources in the Geography and History class in the first cycle of High School. The working method has been qualitative, including semi-structured individual interviews with students and observation of classroom work, with notes in the field notebook,as documentation tools. The main conclusions were that audio-visual tools are very useful for the area of Geography and History, as they allow for the renovation of classroom methodology. They facilitate an understanding increase, activation of previous knowledge, attention and motivation, as they transform a boring content into something more attractive for the students. The students themselves value this, and for this reason they consider it more useful to introduce the subjects with audio-visual media due to their graphic and dynamic nature.